Understanding the light environment within a planar cordon cherry system and its relationship to fruit quality and fruit set : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Horticulture at Massey University, Palmerston North, New Zealand - Scofield, Claire (Massey University, 2022)
New planting systems for cherry trees being investigated in New Zealand, are using reduced inter-row spacing to increase overall light interception, and two-dimensional planar architecture for increasing light distribution through the canopy. As fruit quality is thought to be dependent on the proportional irradiance (light transmission) experienced by the tree’s reproductive structures, these new planting systems are expected to increase fruiting sites and in turn the yield, producing high-quality fruit throughout the canopy. However, in the case of cherries, the level of understanding around both the light environment, and fruit quality distribution using these systems is largely unknown. Therefore, eight-year-old ‘Sweetheart’ cherry trees trained as a planar cordon and spaced at either 1.5 m or 2 m between rows were used to investigate the effects of the light environment within the canopies over the 2020-2021 season on fruit set and fruit quality was evaluated at harvest. Light measurements at four vertical positions within these canopies were taken at 5-minute intervals, from flowering (November 2020) through to harvest (January 2021). Photosynthetically active radiation readings recorded were then used to calculate the daily light integral (DLI). The average canopy DLI for all positions and treatments was found to decrease from flowering through to harvest, using a best fit polynomial model, DLI started at 25 mol mˉ² dˉ¹, and ended the season around 5 mol mˉ² dˉ¹. Variation due to row spacings became evident later in the season, with average monthly DLI higher in the 2 m rows in November and December than in the 1.5 m rows. Vertical position within the canopy had a high correlation with light penetration, with the lowest vertical position (1 m from the ground) in a 2 m row having an almost equivalent mean light environment to the second highest (2 m from the ground) vertical position in a 1.5 m row spacing. Yield, soluble solids concentration (SSC), fruit set and leaf area were all shown to be positively influenced by increased DLI, while diameter was slightly negatively influenced. This influence was generally true for vertical position in the canopy also. Early season DLI had the greatest influence on yield, mid-season DLI had the greatest influence on SSC, and late season DLI had little influence on either fruit set/number or on fruit quality. Introducing reflective mulch into these planar canopy systems was found to improve the light penetration into the lower canopy, however only significantly in the 2 m row spacing. There was little to no influence on fruit quality, fruit set or return bloom.
Keywords: 300802 Horticultural crop growth and development